2012
DOI: 10.2174/156720512799015037
|View full text |Cite
|
Sign up to set email alerts
|

Brain Insulin Resistance and Deficiency as Therapeutic Targets in Alzheimers Disease

Abstract: Alzheimer's disease [AD] is the most common cause of dementia in North America. Despite 30+ years of intense investigation, the field lacks consensus regarding the etiology and pathogenesis of sporadic AD, and therefore we still do not know the best strategies for treating and preventing this debilitating and costly disease. However, growing evidence supports the concept that AD is fundamentally a metabolic disease with substantial and progressive derangements in brain glucose utilization and responsiveness to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
219
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(234 citation statements)
references
References 468 publications
(515 reference statements)
3
219
0
Order By: Relevance
“…41 It has been identified that impaired insulin signaling pathway in the brain might be an important reason to the hyperphosphorylation of tau protein, restoring brain insulin signaling pathway is potentially a novel strategy for treating AD. 42 Catalyzed by the high importance of the brain insulin 37 and the failure of brain insulin therapy for its unexpected and inconvenient, the scientific interest in other factors acting via brain insulin signaling pathway and its downstream AD-associated hyperphosphorylated tau protein began to increase. In this present study, we found that intraperitoneal injection of EX-4, a highly selective GLP-1 receptor agonist, which has been approved for treating T2D, increased insulin signaling pathway in the brain, leading to inhibition of GSK-3β and reversed hyperphosphorylation of tau protein in a rat model of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…41 It has been identified that impaired insulin signaling pathway in the brain might be an important reason to the hyperphosphorylation of tau protein, restoring brain insulin signaling pathway is potentially a novel strategy for treating AD. 42 Catalyzed by the high importance of the brain insulin 37 and the failure of brain insulin therapy for its unexpected and inconvenient, the scientific interest in other factors acting via brain insulin signaling pathway and its downstream AD-associated hyperphosphorylated tau protein began to increase. In this present study, we found that intraperitoneal injection of EX-4, a highly selective GLP-1 receptor agonist, which has been approved for treating T2D, increased insulin signaling pathway in the brain, leading to inhibition of GSK-3β and reversed hyperphosphorylation of tau protein in a rat model of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…The basic concept is that cytotoxic ceramides generated in liver and probably also visceral fat, leak into peripheral blood following injury or cell death caused by local tissue inflammation. Cytotoxic ceramides then traffic through the circulation, and due to their lipid soluble nature, cross the blood–brain barrier and exert neurotoxic and neurodegenerative effects by impairing insulin signaling [7,144,207] and activating pro-inflammatory cytokines [67,208]. This scheme explains how brain insulin resistance, which is an early and important feature of AD, could be mediated by peripheral insulin resistance diseases that are associated with hepatic or visceral fat accumulation, inflammation, dysregulated lipid metabolism, ER/oxidative stress, mitochondrial dysfunction, and activation of pro-death signaling networks [142,144,207].…”
Section: Reverberating Loop Of Insulin/metabolic Malsignaling In Admentioning
confidence: 99%
“…It is the most common form of dementia. Due to the progress in medicine resulting in extended life-span, the number of patients with sporadic form of AD is growing rapidly (de la Monte, 2012). Hence, it is a crucial healthcare problem to assess all risk factors and, consequently, to find proper and effective therapies of pre-AD dementia stages.…”
Section: Introductionmentioning
confidence: 99%